The Effectiveness of Social Media Platforms to the 4th Year Hospitality Management Students in Bestlink College of the Philippines in Choosing Selected Coffee Shops: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Coffee shops are now the fastest-growing business in the world of beverages and arebecoming a well-known trend in the hospitality industry. Moreover, social media has becomean essential marketing tool for coffee shops as it increases brand awareness and engageswith the community. Coffee shops and cafes around the world are discovering social media.This research was conducted to find out the effectiveness of social media platforms on the 4th-year Hospitality management students at Bestlink College of the Philippines in choosingselected coffee shops.The findings show that most coffee shop customers using social media platforms are attractedto unique products and affordable coffee. Active social media are more likely to attract loyalretail customers and stay up-to-date with market trends.When choosing a coffee shop, researchers recommend that business owners have access toit at all times to make it more convenient. It also includes amenities such as drive-thruwindows, comfortable seating, free Wi-Fi, and an easy-to-download mobile app that makes iteasy to recognize as a company when you see that app. In addition, you can stay aware ofnew customer trends to optimize your future posts or improve your products and services tobuild customer relationships. Also, always choose an affordable, budget-friendly, and uniquecafe.
Keywords: Business